Vitamin B12 Deficiency: Causes, Evaluation and Treatment - Smith, Padraic (Trinity Student Medical Journal, 2008)
Vitamin B12 (cobalamin) deficiency is a major public health problem, particularly among the elderly population. It is known that a deficiency in serum B12 levels can cause a combination of neurological and psychiatric disorders. Therefore, in these cases successful replacement of depleted B12 levels is a necessity. Identification of B12 deficiency in elderly patients can be rather difficult as they often tend to present with neurological and neuropsychiatric symptoms despite a lack of haematological evidence showing depleted serum B12 levels. More recently, other parameters such as methylmalonyl-CoA or homocysteine (components of the cobalamin-dependent pathways) have been used as markers of B12 deficiency. Both parameters become elevated upon the onset of B12 deficiency. Several studies have shown that oral B12 replacement therapy can be equally as effective as parenteral (intra-muscular) B12 replacement. Yet, despite these publications, B12 is primarily administered to deficient patients intramuscularly. This inconvenient method of B12 replacement places a rather unnecessary demand on healthcare resources.